2003
DOI: 10.1007/s00240-003-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

Cystine crystal volume determination: a useful tool in the management of cystinuric patients

Abstract: We prospectively determined cystine crystal volume (Vcys) in urine specimens from all consecutive patients with cystine urolithiasis followed at our institution over the past decade, in order to assess its predictive value as to the risk of recurrent cystine stone formation. A total of 57 patients (29 males, 28 females) with homozygous cystinuria entered in the study between January 1990 and December 2000, including 15 children aged less than 15 years and 42 patients aged 15 years or more. The clinical and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 23 publications
3
62
0
4
Order By: Relevance
“…The limited effect of captopril on cystine crystals in comparison to that observed for tiopronine and d-penicillamine is in agreement with clinical findings suggesting the failure of captopril in preventing stone recurrence (Aunsholt & Ahlbom, 1990). Indeed, in our crystalluria studies, we were unable to demonstrate any significant effect of captopril for reducing cystine crystal volume, while a significant decrease in crystal volume was observed in patients treated by either tiopronine or d-penicillamine (Daudon et al, 2003). It is well known that tiopronine and d-penicillamine are able to form soluble complexes with cysteine, thus reducing significantly the amount of cysteine available to form cystine in urine (Meiouet et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The limited effect of captopril on cystine crystals in comparison to that observed for tiopronine and d-penicillamine is in agreement with clinical findings suggesting the failure of captopril in preventing stone recurrence (Aunsholt & Ahlbom, 1990). Indeed, in our crystalluria studies, we were unable to demonstrate any significant effect of captopril for reducing cystine crystal volume, while a significant decrease in crystal volume was observed in patients treated by either tiopronine or d-penicillamine (Daudon et al, 2003). It is well known that tiopronine and d-penicillamine are able to form soluble complexes with cysteine, thus reducing significantly the amount of cysteine available to form cystine in urine (Meiouet et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with our studies on cystine crystalluria related to urine pH: the higher the urine pH, the lower the crystal volume of cystine in urine. Moreover, we have already shown that all patients with a high crystal volume of cystine in urine (above 3000 mm 3 mm À3 ), which corresponds to large crystallite aggregates, developed new stones, while patients with a lower crystal volume did not (Daudon et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…In cystinuric patients, a cystine GCV > 3000 μm 3 /mm 3 of urine was predictive of recurrence of cystine stones, whereas a stable lower value was associated with a lack of recurrence [27]. In all stone formers, crystalluria is more frequent than in healthy subjects, although in these latter some crystals may transiently be found in urine, especially during the hours following a meal.…”
Section: Quantification and Frequency Of Crystalluria In Stone Formersmentioning
confidence: 89%
“…This result is most often attainable in patients with calcium or uric acid nephrolithiasis, while a complete disappearance of crystalluria is more difficult to achieve in inherited disorders such as primary hyperoxaluria type 1 (PH1), cystinuria or dihydroxyadeninuria, which have a very active and permanent crystallization. In these conditions, a decrease in the amount of crystals present in urine samples, expressed as global crystal volume (GCV), is often sufficient to efficiently reduce the lithogenic process [27].…”
Section: Quantification and Frequency Of Crystalluria In Stone Formersmentioning
confidence: 99%
See 1 more Smart Citation